2015
DOI: 10.1021/acs.orglett.5b02731
|View full text |Cite
|
Sign up to set email alerts
|

Auto-Tandem Palladium Catalysis: From Isoxazole to 2-Azafluorenone

Abstract: An auto-tandem palladium catalysis from halogen-substituted isoxazoles and Michael acceptors is described. It involves two mechanistically distinct palladium-catalyzed reactions, a Heck reaction and a rearrangement, leading to 2-azafluorenones. It is the first example of palladium-catalyzed ring opening of isoxazoles and rearrangement of the β-imino ketone ring-opening product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Chen et al. developed a complex auto‐tandem‐catalyzed synthesis of 2‐azafluorenones ( 96 ) from isoxazoles ( 92 ) . This approach made use of two Heck reactions, followed by rearrangement of the isoxazole, thereby forming four new bonds in a single process (Scheme ).…”
Section: Halogensmentioning
confidence: 99%
“…Chen et al. developed a complex auto‐tandem‐catalyzed synthesis of 2‐azafluorenones ( 96 ) from isoxazoles ( 92 ) . This approach made use of two Heck reactions, followed by rearrangement of the isoxazole, thereby forming four new bonds in a single process (Scheme ).…”
Section: Halogensmentioning
confidence: 99%
“…Our group has been interested in developing facile and efficient synthetic methods for biologically active heterocyclic compounds. When exploring new methods for the preparation of the five-membered heterocycles, isoxazoles and isoxazolines, we discovered a palladium-catalyzed rearrangement reaction . Our mechanism study revealed that the reaction involved isoxazole ring-opening as a key step in a cascade reaction sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Our group previously reported a palladium‐catalyzed tandem synthesis of 2‐azafluorenones from isoxazoles . During the course of studying its mechanism, we realized it involved an isoxazole ring‐opening as a key step.…”
Section: Introductionmentioning
confidence: 99%